Chinese revolution : comparative perspectives on transformation of non-western societies - Mohanty, Manoranjan (Delhi : Ajanta Publications, 1992)
Papers originally presented at an international conference held in Hangzhou, China, in November 1987.
Includes bibliographical references.
Keywords: Revolutions; China -- Politics and government -- 1912-1949; China -- Politics and government -- 1949-; China -- Social conditions -- 1912-1949; China -- Social conditions -- 1949-